HAKIKAT PESERTA DIDIK DALAM PENDIDIKAN ISLAM - Nasution, Annisa; Siregar, Nurfadillah; Winanda, Putri; Hanum OK, Azizah (Universitas Maritim AMNI Semarang, 2022)
This study is to find out the understanding of students; knowing the nature of students; Know the characteristics and characteristics of students; and know the elements of students. This study is a literature review in which data is taken from literary sources from experts in the field of Islamic education. The author concludes that students consist of physical/fiscal elements, and spiritual/mental elements. The essence of all learning is to direct students both physically/fiscally and spiritually/mentally to become better and perfect in accordance with the specified learning objectives.